2013
DOI: 10.1002/14651858.cd001073.pub2
|View full text |Cite
|
Sign up to set email alerts
|

D-Penicillamine for preventing retinopathy of prematurity in preterm infants

Abstract: Why it is important to do this reviewThis review updates previous version of the Cochrane review on this intervention (Cochrane 2001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…Although there are few, focused systematic reviews on the prevention of ROP, [87][88][89] this is the first comprehensive meta-analysis of interventions aimed at multiple modifiable risk factors thought to be associated with an increased incidence of ROP. Our review revealed multiple subcategories of postnatal nutritional interventions.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Although there are few, focused systematic reviews on the prevention of ROP, [87][88][89] this is the first comprehensive meta-analysis of interventions aimed at multiple modifiable risk factors thought to be associated with an increased incidence of ROP. Our review revealed multiple subcategories of postnatal nutritional interventions.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In a prospective controlled trial, DPA was administered to preterm infants at 26–35 weeks gestation and found to be effective for ROP with no serious adverse effects (58) and at one year follow-up, (59). Later trials refuted those findings (60,61); Superoxide Dismutase (SOD) dismutates the extremely toxic superoxide anion into H 2 O 2 and H 2 O. SOD is the first line of defense against oxidative stress in the mitochondria, with MnSOD located in the inner mitochondrial matrix. A multicenter trial of intratracheal rhSOD showed a reduction in severe ROP above stage 2 in rhSOD-treated infants born at <25 weeks (62); Lutein and zeaxanthin are antioxidants in the eye.…”
Section: Pharmacologic Interventions In Ropmentioning
confidence: 99%
“…A powerful antioxidant and a VEGF inhibitor, D-penicillamine which when used to treat other disease that premature infants have, the treated infants had less ROP occurrence. However, no significant benefits of D-penicillamine was observed for the outcomes of ROP, death or development of nerves and hence not recommended [21]. Stem cell therapy with the help of umbilical cord blood (UCB) could present as an alternative treatment for ROP in preterm infants.…”
Section: Treatmentmentioning
confidence: 99%